Turkish Drama Serials The Importance and Influence of a Globally Popular Television Phenomenon - Berg, Miriam (University of Exeter Press, 2023)
The extraordinary global success of Turkish drama serials is a significant development in contemporary popular culture. This book presents comparative audience data from three different regions to explore its ramifications across the Global South. We learn how this phenomenon has transformed Turkey-a Muslim-majority country-into the world's second-largest producer of scripted television serials, enticing audiences from all over the world. The book takes an audience-centred approach, investigating the reasons for the allure of Turkish dramas to Arab, Latin American, and Israeli audiences. In tandem, it explores Turkey's changing foreign policy, economic, and trade relationships since the turn of the millennium, which have coincided with the enormous success of the country's television output. It also analyses the role and importance of Turkish dramas as a soft-power tool by scrutinizing how they have influenced viewers' perceptions of Turkey, its people, and its culture. This volume will appeal to those working in various disciplines-from media and communication, international relations, public diplomacy, sociology, and Middle Eastern studies. The material will also be of great relevance to upper-level undergraduates, postgraduate students, academics, scholars and researchers.